2019
DOI: 10.3390/antiox8010026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bioactive Compounds, Mineral Content, and Antioxidant Activity in Bean Varieties Grown with Traditional Methods in Oaxaca, Mexico

Abstract: The aim of the current study is to characterize the bean varieties produced in the State of Oaxaca (Mexico) with the purpose of selecting varieties with the potential of being biofortified with micronutrients. Eleven bean varieties representative of the State of Oaxaca (Mexico) were harvested, the color was characterized and the physicochemical analysis, mineral content, antioxidant capacity, reducing power, and bioactive compounds were determined. Data obtained were subjected to a variance analysis for the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
3
8
2
1
Order By: Relevance
“…W hen combination of application types was assessed, values between 0.76 and 1.64 mg EC3G/g anthocyanins extract were determined and the lowest value corresponded to control value. In general, anthocyanin content determined was similar to that which was reported by Armendáriz-Fernández et al (2019), who assessed varieties of Mexican beans. The combinations producing the greatest levels of anthocyanins that were within the range of dosages reported hare included 0 g edaphic and 25 µM foliar iron, 0.25 g edaphic and 0 µM foliar iron and 0 g edaphic -25 µM foliar iron.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…W hen combination of application types was assessed, values between 0.76 and 1.64 mg EC3G/g anthocyanins extract were determined and the lowest value corresponded to control value. In general, anthocyanin content determined was similar to that which was reported by Armendáriz-Fernández et al (2019), who assessed varieties of Mexican beans. The combinations producing the greatest levels of anthocyanins that were within the range of dosages reported hare included 0 g edaphic and 25 µM foliar iron, 0.25 g edaphic and 0 µM foliar iron and 0 g edaphic -25 µM foliar iron.…”
Section: Resultssupporting
confidence: 86%
“…the greatest activities were observed in plants that were provided a combination 0.25 g edaphic and 0 µM foliar iron, which was statistically similar to the antioxidant activities produced by providing the eight combinations, including the control. Accordingly, Armendáriz-Fernández et al (2019) In this regards you may please reply of the reviewer comments mail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that there is an inverse relationship between morbidity and mortality from degenerative disorders and the ingestion of natural antioxidants [12]. Currently, wild or traditional plants, as a source of natural antioxidants, have received increased attention because of their ability to scavenge ROS and also as sources of trace elements, and their additional health properties, such as antidiabetic, antibacterial and anticancer activity, make them valuable for incorporation into the daily diet [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ocimum sanctum L. leaves reached 73.70% ± 5.87% by DPPH method in the study by Farrukh et al (2006). In relation to seeds, 11 varieties of bean were studied by Armendáriz-Fernández et al (2019) and they were classified into three main groups: (1) high levels, (2) medium levels and (3) low levels of antioxidant capacity. Within the high level of antioxidant capacity are the following bean varieties: Sangre de Toro, Blanco Michigan, Pinto Americano and Flor de Mayo.…”
Section: Antioxidant Activitymentioning
confidence: 99%